2013
DOI: 10.1159/000346305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Presence on Chimpanzee Nest Location in the Lebialem-Mone Forest Landscape, Southwest Region, Cameroon

Abstract: In several areas of Africa, great apes experience increasing predation pressure as a result of human activities. In this study, terrestrial and arboreal nest construction among chimpanzee (Pan troglodytes ellioti) populations was investigated in the Lebialem-Mone Forest Landscape (LMFL), Southwest Region, Cameroon, to examine the anthropogenic effects on nest location. Data on the height, distribution and approximate age of chimpanzee night nests were collected during two 4-week primate field surveys (July to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 40 publications
3
33
0
1
Order By: Relevance
“…This is further supported in chimpanzees [Baldwin et al, 1981;Pruetz et al, 2008;Last and Muh, 2013] and in bonobos [Fruth and Hohmann, 1994]. We did not investigate humidity in our study, therefore we cannot rule out the possibility that the seasonal effect observed is related to humidity.…”
Section: Seasonal and Environmental Factorssupporting
confidence: 52%
See 4 more Smart Citations
“…This is further supported in chimpanzees [Baldwin et al, 1981;Pruetz et al, 2008;Last and Muh, 2013] and in bonobos [Fruth and Hohmann, 1994]. We did not investigate humidity in our study, therefore we cannot rule out the possibility that the seasonal effect observed is related to humidity.…”
Section: Seasonal and Environmental Factorssupporting
confidence: 52%
“…for western lowland gorillas, Gorilla gorilla gorilla , from 7.36% of the time in Petit Loango, Gabon [Furuichi et al, 1997], to 96.2% in La Belgique, Dja Biosphere Reserve, Cameroon . However, bonobos have been observed to ground-nest [Kano, 1983] and chimpanzee ground night nests have increasingly been found to occur in many chimpanzee study sites from east to west [Furuichi and Hashimoto, 2000;Maughan and Stanford, 2001;Koops et al, 2007;Abwe and Morgan, 2008;Pruetz et al, 2008;Hicks, 2010;Last and Muh, 2013], providing evidence of more flexible nesting patterns than previously assumed.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations